2023
DOI: 10.1002/smll.202304686
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical NiCo@NiOOH@CoMoO4 Core–Shell Heterostructure on Carbon Cloth for High‐Performance Asymmetric Supercapacitors

Abdul Rehman Akbar,
Gangqiang Peng,
Yongyi Li
et al.

Abstract: The fabrication of low‐cost, effective, and highly integrated nanostructured materials through simple and reproducible methods for high‐energy‐density supercapacitors is highly desirable. Herein, an activated carbon cloth (ACC) is designed as the functional scaffold for supercapacitors and treated hydrothermally to deposit NiCo nanoneedles working as internal core, followed by a dip‐dry coating of NiOOH nanoflakes core–shell and uniform hydrothermal deposition of CoMoO4 nanosheets serving as an external shell.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Therefore, investigating the relationship between electrode surface properties and electrode activity is of paramount importance for the development of high-performance electrodes. 12,13 Heterostructure is currently a focal point in surface research. Multiple studies have indicated a significant interfacial coupling between highly conductive materials and large electrochemically active materials, enabling high-speed charge transfer and efficient pseudocapacitive activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating the relationship between electrode surface properties and electrode activity is of paramount importance for the development of high-performance electrodes. 12,13 Heterostructure is currently a focal point in surface research. Multiple studies have indicated a significant interfacial coupling between highly conductive materials and large electrochemically active materials, enabling high-speed charge transfer and efficient pseudocapacitive activity.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt molybdate materials, a kind of two-element transitional metal oxide, facilitate reversible redox reactions due to their abundant reserves and variable valence states of cobalt and molybdenum ions, and their electrochemical performance is usually better than that of single-component oxides. Moreover, cobalt and molybdenum ions display rapid electron transfer and good electrical conductivity due to their abilities to form empty d-orbitals after hybridization; therefore, cobalt molybdate (CoMoO 4 ) has been considered one of the most prospective electrode materials for supercapacitors [ 23 , 24 ]. Therefore, using different methods to prepare CoMoO 4 nanomaterials and modify them to obtain high-capacity and high-stability electrode materials has become a research hotspot in the field of supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…The structured core–shell heterostructure electrode showed a capacity of 2.92 F cm −2 at 1 mA cm −2 , while the complex synthesis process increased the uncontrollability of fabrication. 24 Therefore, how to controllably manufacture a 3D hierarchical electrode with high specific capacitance, excellent rate capability and high active material loading at the same time for advanced pseudocapacitance devices is still a huge challenge.…”
Section: Introductionmentioning
confidence: 99%